Co-infection by tick-borne pathogens and Leishmania spp. in dogs with clinical signs suggestive of leishmaniasis from an endemic area in northeastern Brazil - Anna Maria C.F. Evaristo; Paula Talita T. Santos; Felipe S. Sé; Flávia Carolina M. Collere; Bianca B.F. Silva; Ennya R.N. Cardoso; Monica T.A. Kakimori; Thállitha Samih W.J. Vieira; Felipe S. Krawczak; Jonas Moraes-Filho; Rafael F.C. Vieira; Mauricio C. Horta (Pesquisa Veterinária Brasileira, 2024)
ABSTRACT: The present study aimed to investigate the occurrence of Leishmania spp., hemotropic Mycoplasma spp., tick-borne pathogens (TBP), and co-infection in dogs with clinical signs suggestive of visceral leishmaniasis (VL). It also aimed to determine the factors associated with infection and to map the distribution of co-infected dogs in an endemic area in the Northeast region of Brazil. Blood samples from 168 dogs were evaluated for serological analysis to Leishmania spp., Anaplasma spp., Ehrlichia spp., Babesia spp., and molecular assays to Leishmania spp., Anaplasma platys, Ehrlichia canis, Babesia spp., and hemotropic Mycoplasma spp. In serological and molecular analysis, 29.8% and 5.9% of dogs were co-infected. In the regression analysis, seropositivity for Ehrlichia spp., Babesia spp., and Leishmania spp. was significantly associated with the presence of petechiae, young dogs, and weight loss. Serology revealed that co-exposure with Babesia spp. and Ehrlichia spp. was associated with fever and thrombocytopenia, and there was an association between seropositivity for Ehrlichia spp. and Babesia spp. in dogs seropositive for Leishmania spp. The presence of hemotropic Mycoplasma spp. DNA was associated with anorexia. Thus, dogs with clinical VL have co-infection with other pathogens, reinforcing the importance of this study for a better understanding of these co-infections in dogs from endemic areas.